A techno-economic assessment of large scale wind-hydrogen production with energy storage in Western Canada. (8th June 2016) - Olateju, Babatunde; Kumar, Amit; Secanell, Marc
Abstract: Hydrogen production via steam methane reforming (SMR) dominates the supply to refining complexes worldwide, resulting in significant greenhouse gas (GHG) emissions. There is a considerable demand for clean hydrogen pathways that are economically competitive with SMR. The development of a 563 MW integrated wind-hydrogen model with energy storage is proposed. The model utilizes real-time wind energy data to ascertain the optimal size of the electrolyser, the number of electrolyser units and the battery (energy storage) capacity that will yield a minimum hydrogen production cost, whilst functioning in a liberalized electricity market with dynamic prices. The optimal plant configuration consists of 81 units of a 3496 kW (760 Nm 3 /hr) electrolyser and 360 MWh (60 units) of battery capacity. For the minimum hydrogen production cost determined (9.00//kg H2 ), the wind farm accounts for 63% of this cost. Hence, if existing wind farm assets are used, such that the investment cost of building the wind-hydrogen plant does not include the wind farm costs, the hydrogen production cost is reduced to 3.37/kg H2 . For a particular electrolyser-battery configuration, it was observed that the minimum hydrogen production cost occurs when their respective capacity factors are approximately equivalent. The benefits of energy storage are limited by the decrease in overall plant efficiency, which results from the use of the battery. For the techno-economic conditions considered in this paper, hydrogen production costs from wind powered electrolysis (3.37 to 9.00/kg H2 ) are uncompetitive with SMR/SMR-CCS (1.87 to 2.60/kg H2 ). Highlights: An integrated wind-hydrogen plant model with energy storage is developed. A multitude of plant configurations were considered in a liberalized electricity market. Optimum electrolyser and battery sizes – 3496 kW × 81 units and 360 MWh (60 units). Minimum H2 cost achieved varies from 3.37/kg H2 – 9.00/kg H2 . Coincidence of electrolyser and battery capacity factors, yields minimum H2 cost.